PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) RANTAU PULUNG KABUPATEN KUTAI TIMUR - Mujiyanto mujiyanto (ADMINISTRASI PUBLIK, 2020)
Mujiyanto, a thesis with the title of supervision over the work discipline of Public Health Center (Puskesmas) Rantau Pulung District East Kutai Regency. This research aims to know and describe the effect of supervision on the working discipline of Public Health Center (Puskesmas) Rantau Pulung District, East Kutai Regency. Analysis of data using analysis coefficient of product moment correlation, calculation of analysis using SPSS R 17.0 for Windows program. Population in the research of 30 employees, consisting of civil servants (PNS) as many as 23 people and employees TK2D as many as 7 employees at the Public Health Center (Puskesmas) Rantau Pulung District East Kutai. Because the population is not too large, the entire population is made into research respondents using the census method. Based on the results of the data analysis obtained rhit = 0.406, the result is greater when compared to the price-critical price table of the correlation coefficient of Product Moment (Pearson) to n = 30 at a signification rate of 5%, namely 0.229. or it can be said that Rhit = 0.406 > Rtab = 0.229, this means that there is a positive relationship between the monitoring variables of the employee working discipline variables in Rantau Pulung Puskesmas, East Kutai District. The relation of inter-variable supervision to employee work discipline, the result of the calculation is at intervals 0.40 – 0.599, which means that there is a relationship that is in the relationship between the monitoring variables of the personnel working discipline, the result of the calculation is at intervals 0, 40 – 0599, which means that there is a relationship between the supervisory variables with employee discipline variables. Based on the results of the calculation of coefficiencies, the value of R Square or R2 is 0350. This means that variants that occur in employee discipline variables, 35, 0% can be explained through variants that occur in the surveillance variables or in other words that the working discipline of 35, 0% is determined by the supervision of a leader, the Adviesraad is the remainder of 65, 0% determined by other factors or other variables not measured in this study.